Documents and the Undocumented: Urban Anthropology, immigration, and citizenship - Ordóñez, Juan Thomas (Revista de Antropología Social, 2013)
This article explores the everyday life of “undocumented” immigrants working as day laborers on the streets of Northern California by looking at the formal and informal practices of documentation that shape their lives. Through the use of IDs issued by NGOs and other institutions, the immigrants in these pages live and work without formal recognition. Methodologically it is difficult to understand how the dynamics of documentation function because they are based on unstable and ever-changing referents; there are, in other words, no clear rules that determine the use and effects that some documents have. I thus suggest that understanding the documentation practices of a dispersed population living in a vast urban area entails an approach that fits their confusing realities where knowledge of the social world around them is incomplete and ruled by rumor and hearsay.
Keywords: Migration; undocumented immigrants; citizenship; Latin America; United Sates